Science in the City : Culturally Relevant STEM Education - Gates, Lily (Journal of Interdisciplinary Studies in Education, 2023)
In the book, Brown provides an overview of how language and culture play vital roles in science education. Brown (2019) skillfully weaves historical commentary in with pedagogical suggestions to expose readers to the ways in which language, culture, and race impact students of color in science classrooms (p. 23). Brown emphasizes the importance of inclusivity in all classrooms, but specifically the science classroom when he states, “The simple message of Science in the City is that science teaching is the ultimate people business” (p. 25). Because of its focus on student assets, Science in the City reads as the history book every teacher wishes they had, and a practical guidebook for educators on how to incorporate a plethora of voices to form a scientific symphony of diversity.